2011
DOI: 10.1155/2011/541624
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Rubia cordifolia Linn. on Aspirin Plus Pylorus‐Ligated Ulcer

Abstract: The present study was designed to investigate the effect of Rubia cordifolia (Rubiaceae) against experimentally induced gastric ulcer and compare activity with its fractions by employing aspirin plus pylorus-ligated ulcer screening model in Wistar rats. Total acidity, volume of gastric acid secretion, total acid output, and pepsin activity show significant reduction, when compared with the control group. The present study confirmed that chloroform fraction showed the significant activity at lower doses compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Ingestion of food stimulates secretion of hormone gastrin and the vagus nerve which in turn triggers the release of both pepsinogen and HCl in stomach. In the present study Aspirin + pylorus ligation induced increase in secretion of gastric acid and pepsin followed by their accumulation in stomach, which further increased peptic activity 8 . It was observed that pre-treatment with VZ reversed the increased peptic activity by decreasing gastric acid and pepsin secretion associated with aspirin which may further contribute in the treatment of peptic ulcers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Ingestion of food stimulates secretion of hormone gastrin and the vagus nerve which in turn triggers the release of both pepsinogen and HCl in stomach. In the present study Aspirin + pylorus ligation induced increase in secretion of gastric acid and pepsin followed by their accumulation in stomach, which further increased peptic activity 8 . It was observed that pre-treatment with VZ reversed the increased peptic activity by decreasing gastric acid and pepsin secretion associated with aspirin which may further contribute in the treatment of peptic ulcers.…”
Section: Discussionsupporting
confidence: 53%
“…4,5 Remedies from Ayurvedic or traditional medicinal system can be the alternative approach in recent days to overcome the adverse effects of drugs like NSAID's. The use of medicinal plants like Aloe, Terminalia Chebula, Ginseng, Capsicum 6,7 , Rubia cordifolia 8 , Capparis zeylanica 9 , Argyreia speciosa 10 , Jasminum grandiflorum 11 , Heliotropium indicum 12 as drug therapy to treat ulcers has proved to be clinically effective and less relatively toxic than the existing drugs and also reduces the offensive factors serving as a tool in the prevention of peptic ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…Several plant species like Cassia auriculata, Echinops persicus, Rubia cordifolia, Termanilia chebula, Ficus religiosa, Scoparia dulcis [18][19][20][21][22][23] have shown encouraging fi ndings. C. fl exuosus is one such plant, and folklore people of Goutamela used this for the treatment of ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The herbal extracts which are considered being a collection of structurally diverse molecules possess wide therapeutic values such as flavonoids, alkaloids, taninins and phenols which has strong anti-oxidants, anti-inflammatory and anti-microbial properties. In such regards, Rubia cordifolia Linn, a perennial herbaceous climber, 2 possesses anti inflammatory 3 , antibacterial 4 , antioxidant, gastroprotective 5 and many more properties. The present study aimed to evaluate the efficacy of Rubia cordifolia as a single remedy to treat the burn wound healing.…”
mentioning
confidence: 99%